(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the nutritional status and associated factors among children in Huu Lung commune, Lang Son province, in 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 325 children from 6 months to under 12 years old. Anthropometric indicators were measured using standardized procedures, and nutritional status was classified according to WHO 2006/2007 standards. Data on socioeconomic characteristics and micronutrient supplementation were collected through caregiver interviews. The association between nutritional status and micronutrient supplementation was analyzed using the Chi-square test. Results: The proportion of children with normal nutritional status was 60.0%, while stunting accounted for 23.7%, overweight/obesity for 11.7%, and underweight for 4.6%. Only 32% of children received at least one type of micronutrient in the past 12 months, most commonly vitamin D3 (14.8%) and calcium (7.8%). A statistically significant association was observed between micronutrient supplementation and reduced prevalence of stunting (p = 0.0103) and underweight (p = 0.0119). No significant differences were found in the prevalence of normal nutritional status or overweight/obesity between the supplemented and non-supplemented groups. Conclusion: Malnutrition, particularly stunting, remains prevalent among children in Huu Lung. Micronutrient supplementation was significantly associated with lower rates of stunting and underweight, underscoring the essential role of micronutrient interventions in improving child health in mountainous areas.